Method for improving interface bonding strength of thermoelectric device
By plating nickel and tin plating on bismuth telluride-based thermoelectric materials, the porous nanostructure is formed, which solves the problem of low interface bonding strength of bismuth telluride-based thermoelectric devices and improves the reliability and stability of the device.
Patent Information
- Application Number
- CN202411338984.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-31
AI Technical Summary
The bonding strength between Ni and bismuth telluride-based thermoelectric materials in bismuth telluride-based thermoelectric materials is low, resulting in interface cracking and affecting device reliability. Especially after the device is miniaturized, the interface bonding area becomes smaller and the barrier layer is prone to fall off.
Porous nanostructures are formed to enhance interfacial bonding by pretreatment of bismuth telluride-based thermoelectric materials, nickel plating and tin plating, including corrosion, tin plating twice and annealing and strong alkali treatment during the tin plating process.
It significantly improves the interface bonding strength of the thermoelectric device, prevents the barrier layer from falling off, improves the mechanical and thermal stability of the device, and enhances the comprehensive use performance.
Smart Images

Figure CN119221056A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of material surface treatment, in particular to a method for improving the interface bonding strength of a thermoelectric device. Background Art
[0002] Thermoelectric materials are functional materials that can realize the mutual conversion of heat energy and electrical energy, and have broad application prospects in the fields of temperature difference power generation and solid-state refrigeration. Among many thermoelectric materials, bismuth telluride-based thermoelectric materials are currently the thermoelectric materials with the best performance near room temperature, and are also one of the few thermoelectric materials that have achieved large-scale application. With the development of strategic emerging industries such as 5G optical communications, large-scale integrated circuits, and wearable electronic products, higher requirements are placed on the performance of bismuth telluride-based thermoelectric devices.
[0003] Generally speaking, bismuth telluride-based thermoelectric devices are composed of bismuth telluride-based thermoelectric materials, barrier layers, welding layers and ceramic substrates. The performance of thermoelectric devices is not only related to the thermoelectric properties of the materials themselves, but also the combination with the barrier layer interface is particularly important. A high-quality connection interface requires appropriate diffusion reaction between the thermoelectric material and the electrode material, good interface performance, and certain mechanical stability and thermal stability. A large number of studies have shown that Ni is a suitable barrier layer material and can be widely used in thermoelectric elements.
[0004] However, the bonding strength between Ni and bismuth telluride-based thermoelectric materials is often low, which makes the interface cracking of thermoelectric devices easy to occur during long-term use, causing the failure of thermoelectric devices. The interface bonding strength of thermoelectric elements directly determines the reliability of thermoelectric devices, and with the miniaturization of device size, the impact of interface performance on device performance becomes more and more obvious. After the miniaturization of thermoelectric devices, the interface bonding area becomes smaller, and the bonding force also becomes smaller accordingly. The barrier layer is easy to fall off during subsequent cutting, assembly and other processing. Therefore, obtaining higher interface bonding strength is an important research direction to improve the reliability of bismuth telluride-based micro thermoelectric devices. Summary of the invention
[0005] The object of the present invention is to provide a method for improving the interface bonding strength of a thermoelectric device to solve the problems raised in the above background technology.
[0006] To achieve the above object, the present invention provides the following technical solution: A method for improving the interface bonding strength of a thermoelectric device, comprising the following steps:
[0007] (1) Pretreatment: Cut the bismuth telluride-based thermoelectric material crystal rod into wafers of a specified size, then ultrasonically clean it with a cleaning agent; then corrode it with a corrosive solution and then ultrasonically clean it with deionized water;
[0008] (2) Nickel plating: plating a nickel metal layer on the surface of the wafer;
[0009] (3) Tin plating: plating a tin metal layer on the surface of the nickel metal layer;
[0010] The tinning process is performed twice, and between the two tinning processes, the wafer is subjected to annealing treatment and strong alkali treatment in sequence.
[0011] Furthermore, when nickel is plated, the wafer is first placed in a nickel plating activation solution for activation, then electroplated in the nickel plating solution, and finally ultrasonically cleaned with deionized water.
[0012] Further, the tinning process includes:
[0013] First tin plating: firstly, the wafer is activated in a tin plating activation solution, then electroplated in the tin plating solution, and finally ultrasonically cleaned with deionized water;
[0014] Annealing treatment: Heat the wafer at 150-225°C for 2-4 hours;
[0015] Strong alkali treatment: soak the annealed wafer in a strong alkali aqueous solution for 8-12 hours; then use deionized water for ultrasonic cleaning;
[0016] Second tin plating: Activate the wafer in a tin plating activation solution, then electroplate it in the tin plating solution, and finally ultrasonically clean it with deionized water;
[0017] The electroplating time during the second tinning is longer than the electroplating time during the first tinning.
[0018] Furthermore, during the pretreatment process, the etching solution includes: 120-180 g / L sulfuric acid, 100-200 g / L nitric acid and 0-150 ml / L hydrofluoric acid, and the etching time is 1-5 min.
[0019] Furthermore, the cutting method is wire cutting.
[0020] Furthermore, the nickel plating activation solution includes H2SO4 with a concentration of 2-5 mol / L and HCl with a concentration of 0-3 mol / L.
[0021] Furthermore, the nickel plating solution includes: NiSO4·6H2O with a concentration of 300-400 g / L, NiCl2·6H2O with a concentration of 40-60 g / L, H3BO4 with a concentration of 40-60 g / L, a leveling agent with a concentration of 0-1 g / L, and a brightener with a concentration of 0-1 g / L.
[0022] Furthermore, the tin plating activation solution includes: H2SO4 with a concentration of 2-5 mol / L, and HCl with a concentration of 0-3 mol / L.
[0023] Furthermore, the tin plating solution includes: SnSO4 with a concentration of 15-25 g / L, H2SO4 with a concentration of 150-250 g / L, and a brightener with a concentration of 40-60 ml / L.
[0024] Furthermore, the strong alkali aqueous solution is an aqueous solution of KOH, NaOH or Ba(OH)2.
[0025] Compared with the prior art, the method of improving the interface bonding strength of thermoelectric devices of the present invention has the following beneficial effects:
[0026] (1) In the present invention, etching the wafer with an etching solution can form a rough surface on the wafer, thereby increasing the contact area between the nickel atoms in the nickel plating layer and the wafer, which helps to improve the interface bonding strength.
[0027] (2) In the present invention, after the first tin plating is performed on the nickel-plated layer and the tin metal is removed, a porous nanostructure is formed inside the nickel-plated layer. During the second tin plating, the tin atoms enter the porous nanostructure and form a strong anchoring bond with the nickel metal layer, which can further enhance the interface bonding strength.
[0028] (3) In the present invention, the barrier layer includes nickel metal and tin metal that are uniformly interlocked with each other, which can improve the interface bonding strength while fully exerting the barrier properties of the two metals to improve the comprehensive performance of the thermoelectric device. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 : SEM test photograph of the cross section of the product obtained in Example 2.
[0030] Among them, 1: chip layer; 2, nickel-plated layer; 3, tin-plated layer. DETAILED DESCRIPTION
[0031] The present invention provides a method for improving the interface bonding strength of a thermoelectric device, comprising the following steps:
[0032] (1) Pre-treatment:
[0033] Cutting the bismuth telluride-based thermoelectric material crystal rod into wafers of a specified size by a wire cutting process;
[0034] Then the wafer is ultrasonically cleaned with acetone, anhydrous ethanol, and deionized water in sequence, and dried for later use;
[0035] The wafer is placed in an etching solution for chemical etching and then ultrasonically cleaned with deionized water.
[0036] The etching solution includes: 120-180 g / L sulfuric acid, 100-200 g / L nitric acid and 0-150 ml / L hydrofluoric acid, and the etching time is 1-5 min.
[0037] (2) Nickel plating:
[0038] Place the wafer in a nickel plating activation solution containing H2SO4 and activate for 60-120 seconds;
[0039] Then the wafer is placed in a nickel plating solution at 3-6A / dm 2 The current density is 200-400s; the temperature of the nickel plating solution is 60-80℃.
[0040] Finally, ultrasonic cleaning was performed with deionized water.
[0041] The nickel plating activation solution includes H2SO4 with a concentration of 2-5 mol / L and HCl with a concentration of 0-3 mol / L.
[0042] In the nickel plating solution, the concentration of NiSO4·6H2O is 300-400g / L, the concentration of NiCl2·6H2O is 40-60g / L, the concentration of H3BO4 is 40-60g / L, the filling agent is 0-1g / L, and the brightener is 0-1g / L.
[0043] Among them, the filler can be selected from one or more of butynol ether propane sulfonate, propargyl-3-sulfonated propyl ether sodium salt, propargyl alcohol ether propane sulfonate sodium, 1-propyne-3-sulfonate sodium propyl ether, pyridine propane sulfonate, etc.
[0044] Among them, the brightener can be selected from: nickel plating brightener Ni-301 or Ni-809 (Guangdong Bigley Technology Co., Ltd.), HQ990A (Guangzhou Huahuatong Technology Co., Ltd.), HN-998A (Foshan Nanhai Kerui New Materials Co., Ltd.), Jietai PD-107 (Dongguan Jietai Environmental Protection Technology Co., Ltd.), etc. One or more.
[0045] Then tinning begins, and the tinning process includes the following steps:
[0046] (3) First tinning:
[0047] During the first tinning, the wafer is placed in a tinning activation solution containing H2SO4 for activation for 60-120 seconds;
[0048] Then the chip is placed in the tin plating solution at 1-2A / dm 2 Electroplating at a current density of 100-300s;
[0049] After the first tin plating, the wafer is ultrasonically cleaned with deionized water and dried.
[0050] (4) Annealing treatment:
[0051] The wafer is heated at 150-225°C for 2-4 hours to diffuse and fuse the nickel and tin atoms in the coating. The two metal atoms form intermetallic compounds between the layers through thermal diffusion, changing the microstructure of the coating material and making the components in the two coatings uniform.
[0052] (5) Alkali treatment:
[0053] The annealed wafer is immersed in a strong alkaline aqueous solution (KOH, NaOH or Ba(OH)2) for 8-12 hours to remove the metallic tin in the coating and form a nanoporous structure in the nickel coating, and the nanoporous structure is an open-pore structure.
[0054] (6) Second tinning:
[0055] During the second tinning, the wafer is placed in a tinning activation solution containing H2SO4 for activation for 60-120 seconds;
[0056] Then the chip is placed in a tinning bath at 1-3A / dm 2 Electroplating at a current density of 500-800s;
[0057] The tin-plated wafer is ultrasonically cleaned with deionized water and dried.
[0058] Among them, in the first tinning and the second tinning,
[0059] The tin plating activation solution includes H2SO4 with a concentration of 2-5 mol / L and HCl with a concentration of 0-3 mol / L.
[0060] In the tin-plating solution, the concentration of SnSO4 is 15-25g / L, the concentration of H2SO4 is 150-250g / L, and the brightener is 40-60ml / L; and the temperature of the tin-plating solution is 20-25°C.
[0061] Among them, the brightener can be selected from: methanesulfonic acid tin plating brightener, methanesulfonic acid bright tin brightener, SN-518 sulfate bright tin plating brightener purchased from Dongguan Cu Yu New Materials Co., Ltd., or one or more of Q / YS.403 purchased from Guangzhou Yishun Chemical Co., Ltd.
[0062] In the present invention, firstly, the wafer is subjected to wire cutting and chemical etching to form a wafer of suitable size, and a rough surface is formed on the wafer, which is conducive to better bonding of nickel atoms to the wafer surface during the nickel plating process to prevent falling off; then, tin plating is performed twice on the surface of the nickel-plated layer, and the first tin-plated layer is removed with a strong alkali after annealing after electroplating, and a porous nanostructure can be formed in the nickel-plated layer, and the second tin-plated layer can be embedded in the porous nanostructure to form a strong anchoring bond with the nickel layer. In this way, in the final structure, a tight and firm bond is formed between the wafer layer 1, the nickel-plated layer 2, and the tin-plated layer 3 (i.e., the second tin-plated layer), and the interlayer interface bonding strength is greatly improved.
[0063] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0064] Example 1
[0065] A bismuth telluride-based thermoelectric material is prepared, comprising the following steps:
[0066] (1) Pre-treatment:
[0067] Cutting the bismuth telluride-based thermoelectric material crystal rod into wafers of a specified size;
[0068] Then the wafer is ultrasonically cleaned with acetone, anhydrous ethanol, and deionized water in sequence, and dried for later use;
[0069] The wafer was immersed in an etching solution (a mixture of 150 g / L sulfuric acid and 100 g / L nitric acid) for 2 min, and then ultrasonically cleaned with deionized water.
[0070] (2) Nickel plating:
[0071] The wafer was placed in a nickel plating activation solution (containing 2.5 mol / L H2SO4) for activation for 60 seconds;
[0072] Then the wafer was placed in a nickel plating solution (NiSO4·6H2O concentration of 345g / L, NiCl2·6H2O concentration of 45g / L, H3BO4 concentration of 45g / L, filler 1-propyne-3-sulfonic acid sodium propyl ether 0.5g / L, Ni-301 nickel plating brightener 0.5g / L) at 5A / dm 2 The nickel plating process was carried out for 300 s at a current density of , wherein the temperature of the nickel plating solution was 70°C.
[0073] Finally, ultrasonic cleaning was performed with deionized water.
[0074] (3) First tinning:
[0075] The wafer was placed in a tin plating activation solution (containing 2.5 mol / L H2SO4) for activation for 90 seconds;
[0076] Then the wafer is placed in a tinning solution (SnSO4 concentration of 18g / L, H2SO4 concentration of 180g / L, methanesulfonic acid tinning brightener 50ml / L) at 2A / dm 2 The electroplating was carried out for 300s at a current density of , wherein the temperature of the tin plating solution was 25°C.
[0077] After the first tin plating, the wafer is ultrasonically cleaned with deionized water and dried.
[0078] (4) Annealing treatment:
[0079] The wafer is heated at 160°C for 4 hours to diffuse and fuse the nickel and tin atoms in the coating, change the microstructure of the coating material, and homogenize the components in the two coatings.
[0080] (5) Alkali treatment:
[0081] The annealed wafer was placed in a 0.1 mol / L KOH aqueous solution and stirred and immersed for 12 hours to remove the metal tin in the plating layer and form a nanoporous structure in the nickel plating layer. The nanoporous structure is an open-pore structure.
[0082] (6) Second tinning:
[0083] The wafer was placed in a tin plating activation solution (containing 2.5 mol / L H2SO4) for activation for 90 seconds;
[0084] Then the wafer is placed in a tinning solution (SnSO4 concentration of 18g / L, H2SO4 concentration of 180g / L, methanesulfonic acid tinning brightener 50ml / L) at 2A / dm 2 The current density
[0085] The electroplating time is 600s; wherein the temperature of the tin plating solution is 25°C.
[0086] After the second tin plating, the wafer is ultrasonically cleaned with deionized water and dried.
[0087] Example 2
[0088] A bismuth telluride-based thermoelectric material is prepared, comprising the following steps:
[0089] (1) Pre-treatment:
[0090] Cutting the bismuth telluride-based thermoelectric material crystal rod into wafers of a specified size;
[0091] Then the wafer is ultrasonically cleaned with acetone, anhydrous ethanol, and deionized water in sequence, and dried for later use;
[0092] The wafer was immersed in an etching solution (a mixture of 130 g / L sulfuric acid, 150 g / L nitric acid and 100 ml / L hydrofluoric acid) for 2 minutes, and then ultrasonically cleaned with deionized water.
[0093] (2) Nickel plating:
[0094] The wafer was placed in a nickel plating activation solution (containing 2.5 mol / L H2SO4) for activation for 60 seconds;
[0095] The wafer was then plated in a nickel plating solution (NiSO4·6H2O concentration of 350 g / L, NiCl2·6H2O concentration of 450 g / L, H3BO4 concentration of 45 g / L, filler propargyl-3-sulfonated propyl ether sodium salt 0.5 g / L, Ni-809 nickel plating brightener 0.5 g / L) at 4 A / dm 2 The nickel plating process was carried out for 350 seconds at a current density of ; wherein the temperature of the nickel plating solution was 60°C.
[0096] Finally, ultrasonic cleaning was performed with deionized water.
[0097] (3) First tinning:
[0098] The wafer was placed in a tin plating activation solution (containing 2.5 mol / L H2SO4) for activation for 120 s;
[0099] Then the wafer is placed in a tinning solution (SnSO4 concentration of 15g / L, H2SO4 concentration of 200g / L, SN-518 sulfate bright tinning brightener 50ml / L) at 2A / dm 2 The current density is 200s, and the temperature of the tin plating solution is 25℃.
[0100] After the first tin plating, the wafer is ultrasonically cleaned with deionized water and dried.
[0101] (4) Annealing treatment:
[0102] The wafer is heated at 200°C for 2 hours to diffuse and fuse the nickel and tin atoms in the coating, change the microstructure of the coating material, and homogenize the components in the two coatings.
[0103] (5) Alkali treatment:
[0104] The annealed wafer was placed in a 1 mol / L NaOH aqueous solution and stirred and immersed for 10 hours to remove the metal tin in the plated layer and form a nanoporous structure in the nickel plated layer. The nanoporous structure was an open-pore structure.
[0105] (6) Second tinning:
[0106] The wafer was placed in a tin plating activation solution (containing 2.5 mol / L H2SO4) for activation for 90 seconds;
[0107] Then the wafer is placed in a tin plating solution (SnSO4 concentration of 16g / L, H2SO4 concentration of 210g / L, methanesulfonic acid tin plating brightener 50ml / L) at 2A / dm 2 The tin plating process was carried out for 500 s at a current density of ; the temperature of the tin plating solution was 25°C.
[0108] After the second tin plating, the wafer is ultrasonically cleaned with deionized water and dried.
[0109] Example 3
[0110] A bismuth telluride-based thermoelectric material is prepared, comprising the following steps:
[0111] (1) Pre-treatment:
[0112] Cutting the bismuth telluride-based thermoelectric material crystal rod into wafers of a specified size;
[0113] Then the wafer is ultrasonically cleaned with acetone, anhydrous ethanol, and deionized water in sequence, and dried for later use;
[0114] The wafer was immersed in an etching solution (a mixture of 120 g / L sulfuric acid, 100 g / L nitric acid and 100 ml / L hydrofluoric acid) for etching for 3 min, and then ultrasonically cleaned with deionized water.
[0115] (2) Nickel plating:
[0116] The wafer was placed in a nickel plating activation solution (containing 2.5 mol / L H2SO4 and 1 mol / L HCl) for activation for 80 s;
[0117] Then the wafer was placed in a nickel plating solution (NiSO4·6H2O concentration of 360g / L, NiCl2·6H2O concentration of 450g / L, H3BO4 concentration of 45g / L, filler butynol ether propane sulfonate 0.6g / L, HN-998A nickel plating brightener 0.5g / L) at 5A / dm 2 The nickel plating process was carried out for 250 seconds at a current density of ; wherein the temperature of the nickel plating solution was 80°C.
[0118] Finally, ultrasonic cleaning was performed with deionized water.
[0119] (3) First tinning:
[0120] The wafer was placed in a tin plating activation solution (containing 2 mol / L H2SO4 and 1.5 mol / L HCl) for activation for 100 s;
[0121] Then the wafer is placed in a tinning solution (SnSO4 concentration of 16g / L, H2SO4 concentration of 200g / L, SN-518 sulfate bright tinning brightener 50ml / L) at 2A / dm 2 The electroplating time is 150s at a current density of . The temperature of the tin plating solution is 20℃.
[0122] After the first tin plating, the wafer is ultrasonically cleaned with deionized water and dried.
[0123] (4) Annealing treatment:
[0124] The wafer is heated at 220°C for 3 hours to diffuse and fuse the nickel and tin atoms in the coating, change the microstructure of the coating material, and homogenize the components in the two coatings.
[0125] (5) Alkali treatment:
[0126] The annealed wafer was placed in a 0.8 mol / L KOH aqueous solution and stirred and immersed for 9 hours to remove the metal tin in the plating layer and form a nanoporous structure in the nickel plating layer. The nanoporous structure is an open-pore structure.
[0127] (6) Second tinning:
[0128] The wafer was placed in a tin plating activation solution (containing 2 mol / L H2SO4 and 1.5 mol / L HCl) for activation for 90 s;
[0129] Then the wafer is placed in a tinning solution (SnSO4 concentration of 16g / L, H2SO4 concentration of 200g / L, SN-518 sulfate bright tinning brightener 50ml / L) at 2A / dm 2 The electroplating was carried out for 800s at a current density of ; wherein the temperature of the tin plating solution was 20°C.
[0130] After the second tin plating, the wafer is ultrasonically cleaned with deionized water and dried.
[0131] Example 4
[0132] A bismuth telluride-based thermoelectric material is prepared, comprising the following steps:
[0133] (1) Pre-treatment:
[0134] Cutting the bismuth telluride-based thermoelectric material crystal rod into wafers of a specified size;
[0135] Then the wafer is ultrasonically cleaned with acetone, anhydrous ethanol, and deionized water in sequence, and dried for later use;
[0136] The wafer was immersed in an etching solution (a mixture of 120 g / L sulfuric acid and 100 ml / L hydrofluoric acid) for etching for 3 minutes, and then ultrasonically cleaned with deionized water.
[0137] (2) Nickel plating:
[0138] The wafer was placed in a nickel plating activation solution (containing 2.5 mol / L H2SO4) for activation for 80 seconds;
[0139] The wafer was then plated in a nickel plating solution (NiSO4·6H2O concentration of 380 g / L, NiCl2·6H2O concentration of 50 g / L, H3BO4 concentration of 50 g / L, filler propargyl-3-sulfonated propyl ether sodium salt 0.5 g / L, Ni-809 nickel plating brightener 0.5 g / L) at 4 A / dm 2 The nickel plating process was carried out for 300 s at a current density of ; wherein the temperature of the nickel plating solution was 70°C.
[0140] Finally, ultrasonic cleaning was performed with deionized water.
[0141] (3) First tinning:
[0142] The wafer was placed in a tin plating activation solution (containing 2.5 mol / L H2SO4) for activation for 90 seconds;
[0143] Then the wafer is placed in a tinning solution (SnSO4 concentration of 25g / L, H2SO4 concentration of 150g / L, SN-518 sulfate bright tinning brightener 50ml / L) at 3A / dm 2 The electroplating time is 250s at a current density of . The temperature of the tin plating solution is 30℃.
[0144] After the first tin plating, the wafer is ultrasonically cleaned with deionized water and dried.
[0145] (4) Annealing treatment:
[0146] The wafer is heated at 225°C for 2.5 hours to diffuse and fuse the nickel and tin atoms in the coating, change the microstructure of the coating material, and homogenize the components in the two coatings.
[0147] (5) Alkali treatment:
[0148] The annealed wafer was placed in a 1 mol / L KOH aqueous solution and stirred and immersed for 10 hours to remove the metal tin in the plated layer and form a nanoporous structure in the nickel plated layer. The nanoporous structure was an open-pore structure.
[0149] (6) Second tinning:
[0150] The wafer was placed in a tin plating activation solution (containing 2.5 mol / L H2SO4) for activation for 90 seconds;
[0151] Then the wafer is placed in a tin plating solution (SnSO4 concentration of 25g / L, H2SO4 concentration of 150g / L, methanesulfonic acid tin plating brightener 50ml / L) at 3A / dm 2 The electroplating was carried out for 700s at a current density of ; wherein the temperature of the tin plating solution was 30°C.
[0152] After the second tin plating, the wafer is ultrasonically cleaned with deionized water and dried.
[0153] Example 5
[0154] A bismuth telluride-based thermoelectric material is prepared, comprising the following steps:
[0155] (1) Pre-treatment:
[0156] Cutting the bismuth telluride-based thermoelectric material crystal rod into wafers of a specified size;
[0157] Then the wafer is ultrasonically cleaned with acetone, anhydrous ethanol, and deionized water in sequence, and dried for later use;
[0158] The wafer was immersed in an etching solution (a mixture of 150 g / L sulfuric acid, 130 g / L nitric acid and 100 ml / L hydrofluoric acid) for etching for 3 minutes, and then ultrasonically cleaned with deionized water.
[0159] (2) Nickel plating:
[0160] The wafer was placed in a nickel plating activation solution (containing 2 mol / L H2SO4) for activation for 60 seconds;
[0161] The wafer was then plated in a nickel plating solution (NiSO4·6H2O concentration of 320 g / L, NiCl2·6H2O concentration of 50 g / L, H3BO4 concentration of 50 g / L, filler propargyl-3-sulfonated propyl ether sodium salt 0.4 g / L, Ni-809 nickel plating brightener 0.7 g / L) at 5 A / dm 2 The nickel plating solution was electroplated for 280 seconds at a current density of 70°C.
[0162] Finally, ultrasonic cleaning was performed with deionized water.
[0163] (3) First tinning:
[0164] The wafer was placed in a tin plating activation solution (containing 2.5 mol / L H2SO4) for activation for 120 s;
[0165] Then the wafer is placed in a tinning solution (SnSO4 concentration of 15g / L, H2SO4 concentration of 170g / L, SN-518 sulfate bright tinning brightener 50ml / L) at 2A / dm 2The electroplating time is 150s at a current density of . The temperature of the tin plating solution is 20℃.
[0166] After the first tin plating, the wafer is ultrasonically cleaned with deionized water and dried.
[0167] (4) Annealing treatment:
[0168] The wafer is heated at 150°C for 4 hours to diffuse and fuse the nickel and tin atoms in the coating, change the microstructure of the coating material, and homogenize the components in the two coatings.
[0169] (5) Alkali treatment:
[0170] The annealed wafer was placed in a 0.8 mol / L NaOH aqueous solution and stirred and immersed for 10 hours to remove the metal tin in the plated layer and form a nanoporous structure in the nickel plated layer. The nanoporous structure is an open-pore structure.
[0171] (6) Second tinning:
[0172] The wafer was placed in a tin plating activation solution (containing 2.5 mol / L H2SO4) for activation for 90 seconds;
[0173] Then the wafer is placed in a tin plating solution (SnSO4 concentration of 15g / L, H2SO4 concentration of 160g / L, methanesulfonic acid tin plating brightener 50ml / L) at 2A / dm 2 The electroplating was carried out for 800s at a current density of ; wherein the temperature of the tin plating solution was 20°C.
[0174] After the second tin plating, the wafer is ultrasonically cleaned with deionized water and dried.
[0175] Comparative Example 1
[0176] (1) Pre-treatment:
[0177] Cutting the bismuth telluride-based thermoelectric material crystal rod into wafers of a specified size;
[0178] Then the wafer is ultrasonically cleaned with acetone, anhydrous ethanol, and deionized water in sequence, and dried for later use;
[0179] (2) Nickel plating:
[0180] The wafer was placed in a nickel plating activation solution (containing 3 mol / L H2SO4) for activation for 60 seconds;
[0181] Then the wafer was placed in a nickel plating solution (NiSO4·6H2O concentration of 345g / L, NiCl2·6H2O concentration of 45g / L, H3BO4 concentration of 45g / L, filler 1-propyne-3-sulfonic acid sodium propyl ether 0.5g / L, Ni-301 nickel plating brightener 0.5g / L) at 5A / dm 2 The nickel plating process was carried out for 300 s at a current density of ; wherein the temperature of the nickel plating solution was 70°C.
[0182] Finally, ultrasonic cleaning was performed with deionized water.
[0183] (3)Tin plating:
[0184] The wafer was placed in a tin plating activation solution (containing 3.5 mol / L H2SO4) for activation for 90 seconds;
[0185] Then the wafer is placed in a tin plating solution (SnSO4 concentration of 20g / L, H2SO4 concentration of 200g / L, methanesulfonic acid tin plating brightener 50ml / L) at 2A / dm 2 The current density is 20°C and the electroplating time is 300s.
[0186] After the first tin plating, the wafer is ultrasonically cleaned with deionized water and dried.
[0187] Comparative Example 2
[0188] (1) Pre-treatment:
[0189] Cutting the bismuth telluride-based thermoelectric material crystal rod into wafers of a specified size;
[0190] Then the wafer is ultrasonically cleaned with acetone, anhydrous ethanol, and deionized water in sequence, and dried for later use;
[0191] (2) Nickel plating:
[0192] The wafer was placed in a nickel plating activation solution (containing 2.5 mol / L H2SO4) for activation for 60 seconds;
[0193] Then the wafer was placed in a nickel plating solution (NiSO4·6H2O concentration of 345g / L, NiCl2·6H2O concentration of 45g / L, H3BO4 concentration of 45g / L, filler 1-propyne-3-sulfonic acid sodium propyl ether 0.5g / L, Ni-301 nickel plating brightener 0.5g / L) at 5A / dm 2 Electroplating for 250s at a current density of
[0194] Finally, ultrasonic cleaning was performed with deionized water.
[0195] (3) First tinning:
[0196] The wafer was placed in a tin plating activation solution (containing 2.5 mol / L H2SO4) for activation for 90 seconds;
[0197] Then the wafer is placed in a tinning solution (SnSO4 concentration of 18g / L, H2SO4 concentration of 180g / L, methanesulfonic acid tinning brightener 50ml / L) at 2A / dm 2 The current density is 20°C and the electroplating time is 300s.
[0198] After the first tin plating, the wafer is ultrasonically cleaned with deionized water and dried.
[0199] (4) Second tinning:
[0200] The wafer was placed in a tin plating activation solution (containing 2.5 mol / L H2SO4) for activation for 90 seconds;
[0201] Then the wafer is placed in a tin plating solution (SnSO4 concentration of 18g / L, H2SO4 concentration of 180g / L, methanesulfonic acid tin plating brightener 50ml / L) at 2A / dm 2 The tin plating process was carried out for 600 s at a current density of ; wherein the temperature of the tin plating solution was 20°C.
[0202] After the second tin plating, the wafer is ultrasonically cleaned with deionized water and dried.
[0203] Comparative Example 3
[0204] (1) Pre-treatment:
[0205] Cutting the bismuth telluride-based thermoelectric material crystal rod into wafers of a specified size;
[0206] Then the wafer is ultrasonically cleaned with acetone, anhydrous ethanol, and deionized water in sequence, and dried for later use;
[0207] (2) Nickel plating:
[0208] The wafer was placed in a nickel plating activation solution (containing 2.5 mol / L H2SO4) for activation for 60 seconds;
[0209] Then the wafer was placed in a nickel plating solution (NiSO4·6H2O concentration of 345g / L, NiCl2·6H2O concentration of 45g / L, H3BO4 concentration of 45g / L, filler 1-propyne-3-sulfonic acid sodium propyl ether 0.5g / L, Ni-301 nickel plating brightener 0.5g / L) at 5A / dm 2 Electroplating for 300s at a current density of
[0210] Finally, ultrasonic cleaning was performed with deionized water.
[0211] Finally, perform a performance test:
[0212] (1) Interface strength test:
[0213] The samples in the embodiments and comparative examples were selected for the interface bonding strength test, and the interface bonding strength between the wafer and the barrier layer was tested with reference to the method in GB / T5270-2005 Review of Adhesion Strength Test Methods for Electrodeposited and Chemically Deposited Metal Coatings on Metal Substrates. The test results are shown in Table 1.
[0214] Table 1 Interface bonding strength between wafer layer and barrier layer in Examples and Comparative Examples
[0215]
[0216]
[0217] (2) The cross section of the product obtained in Example 2 was subjected to SEM testing. Figure 1 As shown, the results show that there is an uneven interface between the chip layer 1, the nickel-plated layer 2 of the barrier layer and the tin-plated layer 3, which greatly improves the interface bonding strength between the chip layer and the barrier layer.
[0218] In the present invention, only a method for preparing a barrier layer on a bismuth telluride-based wafer material is provided. The preparation of a welding layer and a ceramic substrate in a thermoelectric device can be carried out by referring to the prior art and will not be described in detail here.
[0219] In summary, the present invention provides a method for improving the interface bonding strength in a thermoelectric device. In the obtained bismuth telluride-based thermoelectric material, the interface bonding strength between the bismuth telluride chip material and the barrier layer is high, which can effectively prevent the barrier layer material from falling off and improve the stability of the thermoelectric material during its service life.
[0220] The above embodiments are merely descriptions for the purpose of clearly illustrating the present invention, and are not limitations on the implementation methods. For those skilled in the art, other different forms of changes or modifications may be made based on the above descriptions. It is not necessary and impossible to enumerate all the implementation methods here, and the obvious changes or modifications derived therefrom are still within the scope of protection of the present invention.
Claims
1. A method for improving the interface bonding strength of a thermoelectric device, characterized in that: The steps include: (1) Pretreatment: Cut the bismuth telluride-based thermoelectric material crystal rod into wafers of a specified size, then ultrasonically clean it with a cleaning agent; then corrode it with a corrosive solution and then ultrasonically clean it with deionized water; (2) Nickel plating: plating a nickel metal layer on the surface of the wafer; (3) Tin plating: plating a tin metal layer on the surface of the nickel metal layer; The tinning process is performed twice, and between the two tinning processes, the wafer is subjected to annealing treatment and strong alkali treatment in sequence.
2. The method for improving the interface bonding strength of a thermoelectric device according to claim 1, characterized in that: When nickel plating, the wafer is first placed in a nickel plating activation solution for activation, then electroplated in the nickel plating solution, and finally ultrasonically cleaned with deionized water.
3. The method for improving the interface bonding strength of a thermoelectric device according to claim 1, characterized in that: The tinning process comprises: First tin plating: firstly, the wafer is activated in a tin plating activation solution, then electroplated in the tin plating solution, and finally ultrasonically cleaned with deionized water; Annealing treatment: Heat the wafer at 150-225°C for 2-4 hours; Strong alkali treatment: soak the annealed wafer in a strong alkali aqueous solution for 8-12 hours; then use deionized water for ultrasonic cleaning; Second tin plating: Activate the wafer in a tin plating activation solution, then electroplate it in the tin plating solution, and finally ultrasonically clean it with deionized water; The electroplating time during the second tinning is longer than the electroplating time during the first tinning.
4. The method for improving the interface bonding strength of a thermoelectric device according to claim 1, characterized in that: In the pre-treatment process, the etching solution includes: 120-180 g / L sulfuric acid, 100-200 g / L nitric acid and 0-150 ml / L hydrofluoric acid, and the etching time is 1-5 min.
5. The method for improving the interface bonding strength of a thermoelectric device according to claim 1, characterized in that: The cutting method is wire cutting.
6. The method for improving the interface bonding strength of a thermoelectric device according to claim 2, characterized in that: The nickel plating activation solution includes H2SO4 with a concentration of 2-5 mol / L and HCl with a concentration of 0-3 mol / L.
7. The method for improving the interface bonding strength of a thermoelectric device according to claim 2, characterized in that: The nickel plating solution comprises: NiSO4·6H2O with a concentration of 300-400 g / L, NiCl2·6H2O with a concentration of 40-60 g / L, H3BO4 with a concentration of 40-60 g / L, a leveling agent with a concentration of 0-1 g / L, and a brightener with a concentration of 0-1 g / L.
8. The method for improving the interface bonding strength of a thermoelectric device according to claim 3, characterized in that: The tin plating activation solution includes: H2SO4 with a concentration of 2-5 mol / L and HCl with a concentration of 0-3 mol / L.
9. The method for improving the interface bonding strength of a thermoelectric device according to claim 3, characterized in that: The tin plating solution comprises: SnSO4 with a concentration of 15-25 g / L, H2SO4 with a concentration of 150-250 g / L, and a brightener with a concentration of 40-60 ml / L.
10. The method for improving the interface bonding strength of a thermoelectric device according to claim 3, characterized in that: The strong alkali aqueous solution is an aqueous solution of KOH, NaOH or Ba(OH)2.
